Psychological and behavioral dimensions in cardiac arrest survivors and their families: A state-of-the-art review - Sachin Agarwal; Mette Kirstine Wagner; Marco Mion (Neurotherapeutics)
This article aims to highlight high-quality observational and intervention studies focused on promoting psychological well-being among cardiac arrest (CA) survivors and their families. Following CA, many patients experience significant psychological distress, including depression, generalized anxiety, and post-traumatic stress. Recent studies indicate that this distress can narrow patients’ focus, resulting in heightened awareness of cardiac signals—such as fluctuations in heart rate or blood pressure—that lead to constant monitoring and increased anxiety. This anxiety, compounded by behavioral avoidance toward cardioprotective behaviors and physiological hyperarousal, may elevate the risk of secondary cardiovascular diseases and adversely affect the quality of life. Current research is exploring behavioral interventions aimed at reducing this psychological distress, strategies to enhance coping mechanisms, and improving overall health in the survivor-family dyad. Unlike other cardiovascular conditions, no clinical practice guidelines exist for assessing or treating the psychological consequences of CA. Future research should prioritize identifying and treating modifiable psychological factors using targeted therapies and behavioral interventions.